Teaching according to the multiple intelligences prevailing among the students of the faculty of languages and administration at the international Islamic University in Malaysia from their point of view - Mohammad Khalil Mohammad AlRamadeen (Penerbit Universiti Kebangsaan Malaysia, 2023)
The aim of the current research is to identify the predominant patterns of multiple intelligences among students of the College of Languages and Management, Arabic Department, at the International Islamic University in Malaysia, and to outline classroom activities that align with the dominant intelligences of students in the Arabic language department at the college. The research adopts a descriptive methodology, and the research sample consists of 65 male and female students from the Arabic language department of the College of Languages and Management at the International Islamic University in Malaysia. The research results indicate that the arithmetic means of the Multiple Intelligence Scale among Arabic language students in the College of Languages and Management range between 2.95 and 3.64. The Personal Intelligence scale achieved the highest average score at 3.64, followed by Linguistic Intelligence with an average of 3.44. The research then identifies a set of classroom activities and exercises based on paragraphs that are partially or fully applicable. These activities are categorized into three groups: activities specific to linguistic intelligence, activities specific to spatial intelligence, and activities for other multiple intelligences based on their paragraphs that achieved alignment.